Kajian Pemetaan Tenaga Kerja Konstruksi Berkelanjutan Level Operator di Kabupaten Tangerang - Sarjono Puro; Kiki Maria; Edison H. Manurung; Charles Sitindaon (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Investment realization in Tangerang Regency increased steadily from 2020 to 2024, reaching a cumulative value of IDR 26.2 trillion in 2024. This growth was supported by major infrastructure projects in Banten Province, including the Serang-Panimbang Toll Road Sections 2A and 2B and the Serpong-Balaraja Toll Road Section 1B. These projects have expanded employment opportunities for construction workers, particularly operator-level workers. However, limited workforce competency remains a challenge to construction project performance. Previous studies indicate that competency is influenced by education, technical skills, and work experience, while many construction workers still lack formal competency certification. This study aims to map the characteristics and competency profile of operator-level construction workers in Tangerang Regency. A quantitative descriptive approach combined with cluster analysis was employed to analyze worker characteristics and competency levels. The results show that operator-level construction workers are predominantly 40 to 50 years old (70.48%), male (100%), have completed only elementary education (43%), are local residents (92%), and have more than six years of work experience (60.42%). Most have worked on residential construction projects (76%) and typically wait zero to six months for their next project (71%). Nevertheless, 84% have never attended formal training and 87% do not possess a Construction Work Competency Certificate (SKK). These findings highlight the need to expand training and certification programs to improve workforce competency and support sustainable construction development.